2021
DOI: 10.1108/jedt-04-2021-0189
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the benefits of cloud computing for sustainable construction in Nigeria

Abstract: Purpose Cloud computing is one of the digitalization principles used in some sectors like banking, health and construction industry. This paper aims to examine the benefits of applying cloud computing for construction sustainability in Nigeria. Design/methodology/approach The cloud computing benefits-related data were retrieved from previous studies and complemented with a questionnaire survey to obtain data from stakeholders involved in the execution of construction projects in Lagos State, Nigeria, through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…For factor analysis, the varimax rotation is more suitable. It is an unresolved standard concept that abridges factors (Costello and Osborne, 2005; Oke et al , 2021a). The total variables would be observed as a typical sample around the relevant ranges (Tabachnick et al , 2007).…”
Section: Study Methods and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…For factor analysis, the varimax rotation is more suitable. It is an unresolved standard concept that abridges factors (Costello and Osborne, 2005; Oke et al , 2021a). The total variables would be observed as a typical sample around the relevant ranges (Tabachnick et al , 2007).…”
Section: Study Methods and Designmentioning
confidence: 99%
“…The second section rated the CC tools using a 5-point Linkert scale: 5 (very high), 4 (high), 3 (average), 2 (low) and 1 (very low). It is widely applied in the literature (Kineber et al, 2020a(Kineber et al, , 2020bAl-Mekhlafi et al, 2021;Oke et al, 2021a). Many well-defined variables for the factorability of a relationship have been applied.…”
Section: The Exploratory Factor Analysis For Cloud Computing Of Toolsmentioning
confidence: 99%
“…Tunji-Olayeni et al (2020) identified common sustainable practices to include compliance with health and safety regulation, waste management, energy efficiency and material reuse. Additionally, around this time, Babalola (2020) (Okoye and Okolie, 2013;Babawale and Oyalowo, 2013;Aghimiena et al, 2019;Oke et al, 2021;Adekunye and Oke, 2022;Isang and Ebiloma, 2023) have explored different aspects of sustainability in construction projects. Abolore (2012) and Okoye and Okolie (2013) applied environmental and social perspective to SC by showing that imbibing environmental protection and safety culture through management commitment, safety training and education, and instituting regulatory framework promotes SC practice in Nigeria.…”
Section: 3mentioning
confidence: 99%
“…In the second section, they were also asked to evaluate the barriers preventing VM implementation via a five-point Likert scale. On the scale, “5 was very high, 4 high, 3 average, 2 low and 1 very low.” This scale has been used in some previous studies (Oke et al , 2021; Buniya et al , 2021; Al-Mekhlafi et al , 2021). The details of the data collection, through two questionnaire surveys, are described in the following paragraphs.…”
Section: Data Collectionmentioning
confidence: 99%